2007
DOI: 10.20870/oeno-one.2007.41.4.835
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the flower stage and culture medium on the induction of somatic embryogenesis from anther culture in Tunisian grapevine cultivars

Abstract: <p style="text-align: justify;"><strong>Aims</strong>: The aim of this research is to identify the optimal flower developmental stage, in order to establish an efficient regeneration protocol via somatic embryogenesis in several local grapevine (Vitis vinifera L.) cultivars, using anther culture.</p><p style="text-align: justify;"><strong>Methods and results</strong>: Immature anthers sampled on fruity cuttings, at three flower developmental stages were cultured on thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…We measured only the flower bud length to discriminate between old and young flower buds because Cardoso et al [64] have shown a high correlation of flower bud length with anther and ovary development (r = 0.83) in cv. Aragonez and Bouamama et al [48] confirmed this in nine diverse cultivars. The two stages correspond to the premeiotic and uninucleate stages of pollen development as described by Gribaudo et al [50] and Cardoso et al [64].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We measured only the flower bud length to discriminate between old and young flower buds because Cardoso et al [64] have shown a high correlation of flower bud length with anther and ovary development (r = 0.83) in cv. Aragonez and Bouamama et al [48] confirmed this in nine diverse cultivars. The two stages correspond to the premeiotic and uninucleate stages of pollen development as described by Gribaudo et al [50] and Cardoso et al [64].…”
Section: Discussionmentioning
confidence: 71%
“…Since these early studies, the most frequently used explants for successful SE in grapevines have been derived from floral tissue. These include ovules [46,47], anthers [7,[48][49][50][51][52], pistils [6,21], stigmas and styles [33,53], ovaries [54][55][56][57] and the whole flower [55]. It is clear that the efficiency of SE is dependent on the explant used and the maturity of the explant [45,50,55,58], the media constituents [3,49,51,59,60] and the genotype [20,49,55,59].…”
Section: Introductionmentioning
confidence: 99%
“…1 . Initiation of direct somatic embryo formation was generated on the cut edges and filaments surfaces, when cultured on modified CP enriched with 2 mg l −1 2,4-D and 2.5 mg l −1 TDZ, as employed by Bouamama et al (2007 , 2009) . To inhibit any callus formation, our cultures were exposed to luminosity since culture initiation.…”
Section: Resultsmentioning
confidence: 99%
“…After removing flowers capuchin, stamens were plated on 9 cm Petri dishes containing modified Chée and Pool (1987) based-medium (CP), supplemented with 150 mg l −1 myo-inositol, 100 mg l −1 Fe-EDTA, 200 mg l −1 glutamine, 30 g l −1 sucrose and solidified with 3 g l −1 Gelrite. The CP based medium was enriched with 2 mg l −1 2,4-dichlorophenoxyacetic acid (2,4-D) and 2.5 mg l −1 of N-Phenyl-N′-(1,2,3-thiadiazol-5-yl) urea (Thidiazuron, TDZ) ( Bouamama et al, 2007 ). The cultures were incubated in a culture room at 24 ± 1ºC in a 16-hour light at an intensity of 100 μE m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…In fact, to the best of our knowledge, published works on in vitro regeneration of the local Tunisian chickpea, and particularly on its somatic embryogenesis are absent. Previous Tunisian somatic embryogenesis studies has been carried out only on Cucumis melo L. (Rhimi et al, 2006), Vitis vinifera L. (Bouamama et al, 2007;, Ceratonia siliqua L. (Ksia et al, 2008) and Phoenix dactylifera L. (Othmani et al, 2018).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%